Body Louse Pathogen Surveillance among Persons Experiencing Homelessness, Canada, 2020–2021 - Carl Boodman; Leslie R. Lindsay; Antonia Dibernardo; Kathy Kisil; Heather Coatsworth; Chris Huynh; Amila Heendeniya; John Schellenberg; Yoav Keynan (Emerging Infectious Diseases, 2024)
We analyzed body lice collected from persons experiencing homelessness in Winnipeg, Manitoba, Canada, during 2020–2021 to confirm vector species and ecotype and to identify louseborne pathogens. Of 556 lice analyzed from 7 persons, 17 louse pools (218 lice) from 1 person were positive for the louseborne bacterium Bartonella quintana.